False positives and false negatives measure less than 0.001% in labeling ssDNA with osmium tetroxide 2,2’-bipyridine - Kanavarioti, Anastassia (Beilstein Journal of Nanotechnology, 2016)
Osmium tetroxide 2,2’-bipyridine (OsBp) is known to react with pyrimidines in ssDNA and preferentially label deoxythymine (T) over deoxycytosine (C). The product, osmylated DNA, was proposed as a surrogate for nanopore-based DNA sequencing due to OsBp’s “perfect” label attributes. Osmylated deoxyoligos translocate unassisted and measurably slow via sub-2 nm SiN solid-state nanopores, as well as via the alpha-hemolysin (α-HL) pore. Both nanopores discriminate clearly between osmylated and intact nucleobase; α-HL was also shown to discriminate between osmylated T and osmylated C. Experiments presented here confirm that the kinetics of osmylation are comparable for short oligos and long ssDNA and show that pyrimidine osmylation is practically complete in two hours at room temperature with less than 15 mM OsBp. Under the proposed labeling conditions: deoxyoligo backbone degradation measures less than 1/1,000,000; false positives such as osmylated deoxyadenine (A) and osmylated deoxyguanine (G) measure less than 1/100,000; false negatives, i.e., unosmylated C measure less than 1/10,000; and unosmylated T must measure substantially lower than 1/10,000 due to the 27-fold higher reactivity of T compared to C. However, osmylated C undergoes degradation that amounts to about 1–2% for the duration of the labeling protocol. This degradation may be further characterized, possibly suppressed, and the properties of the degradation products via nanopore translocation can be evaluated to assure base calling quality in a DNA sequencing effort.
Keywords: α-hemolysin; capillary electrophoresis; DNA sequencing; high-performance liquid chromatography; nanopores; osmium tetroxide bipyridine; osmylated oligos; osmylation; ssDNA